PENGARUH REPUTASI KANTOR AKUNTAN PUBLIK DAN KOMITE AUDIT TERHADAP LAPORAN INTEGRITAS KEUANGAN DENGAN PEMODERASI CORPORATE GOVERNANCE (Studi Empiris Pada Persahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Rizkiyatul Awalin; Abdul Wahid Mahsuni; Hariri Hariri (Universitas Islam Malang, 2020)
The purpose of this study were:1) to test the effect of the reputation of public accounting firms and audit committees simultaneously influence on the integrity of financial statements 2) to examine the reputation of the public accounting firm to the integrity of the financial statements 3) to examine the audit committee to the integrity of the financial statements 4) to examine corporate governance proxied by independent directors and institutional ownership strengthening the influence of the reputation of the public accounting firm to the integrity of financial statements 5) to examine corporate governance and ownership proxied by independent commissioner institutional strengthen the influence of the audit committee to the integrity financial statements. Using a sample of manufacturing companies listed in Indonesia Stock Exchange and the study period 2016-2018. The results of this study show that the reputation of public accounting firms affect the integrity of financial statements. Audit committee firms affect the integrity of financial statement. Corporate governance strengthening the influence of the reputation of the public accounting firm to the integrity of financial statement. Corporate governance strengthening the influence of the audit committee to the integrity to the financial statements and reputable accounting public firma and audit committee affect simultaneously to the integrity of financial statements.Keywords: Public accounting firm's reputation, Audit committee, Integrity financial reporting, Corporate governance.